Feminization of Teaching in Bangladesh: Exploring the Influence of State, Market, and Family - Shamnaz Arifin Mim (STKIP Singkawang, 2020)
Although the number of women teachers is increasing in primary schools, the profession is often devalued considering social prestige and remuneration. This review article thus aims to explore the ways in which existing structures of the state, markets, and families in Bangladesh are leading to feminize primary school teaching. By adopting a gender lens, this study is mainly supported by kinds of literature, policy documents, and guidelines were ‘teaching as a feminized profession’ has been conceptualized in a global-local context. The study argues that states’ existing policies regarding primary school teaching is politicized in a way that it encourages women and devalues the profession at the same time. This critical descriptive review reveals how income status within the home can shape masculine and feminine work experiences and how the whole process of teaching gets cheaper with the presupposed gender-roles. The household ideology within patriarchal structures encourages women to pursue this profession which provides them enough time to take care of the family. Finally, the societal fabrics of the market and heteronormative ideas of family are found as intertwined with the state’s intervention to feminize primary school teaching. This study would therefore hopefully lead to change gendered mindsets of not only the policymakers but also of both the men and women themselves who should pursue primary teaching as a profession where they genuinely can contribute regardless of their gender-roles.